Strategic Challenges in Neurotherapeutic Pharmaceutical Development - Gallen, Christopher C. (The American Society for Experimental NeuroTherapeutics, Inc., 2004)
Summary: Developing new therapeutics presents formidable economic, scientific, and medical challenges that are exacerbated by special factors in neurotherapeutics development, e.g., the complexity of the CNS with its attendant need to sometimes affect multiple pathways, the lack of clarity of disease etiology, inadequacy of available animal models, and difficulties in defining disease populations and quantifying treatment response. This paper reviews the economic challenges faced by therapeutics developers in general and neurotherapeutics developers in particular. It discusses key scientific challenges, particularly those pertinent to neurotherapeutics development, as a background to proposing a different industrial strategy to drive future therapeutics development. This Biodesign strategy potentially surpasses previous paradigms by incorporating elements such as the use of disease modeling to select better targets and potential therapies, information science-based approaches to enhance small molecule chemistry, exploitation of the potential for biological technologies to rapidly generate mechanistic probes, and development of improved approaches for using animal models and studying human molecules mechanistically and biologically. Synergistic use of these elements can change the overall business model of companies engaged in neurotherapeutics development. The Biodesign paradigm has the potential to both markedly enhance the development of new therapies and to address some of the economic challenges facing healthcare systems and therapeutics developers alike.